Gold as part of the goal in society - ISMAIL, ROSAFFIE; TASLIM, MOHD RAZIF HAFIZ (Human Sustainability Procedia, 2018)
This study aims at discussing as well as to find the solution to reduce the hardcore poverty in some communities using gold as part of the portfolio of savings. In this study the emphasis will begin to cover the introduction of gold and its types and how this commodity really helps those in need to hedge against inflation. Next the study also covers the method of education among society to let them realise why it is important and how the consistent increase in price is overcome using the precious metal and finally this study also explains what are the challenges to let the society understand the role of goldKeyword: gold, inflation, education , challenges